ANALISIS MANAJEMEN RISIKO PEMBIAYAAN DAN PENGELOLAAN PRODUK PPR IB MASLAHAH DI BJB SYARIAH KCP. KUNINGAN - Alfarizi, Faiz Raka; Zahra, Qiny Shonia Az (JURNAL EKONOMI SYARIAH, 2021)
Housing is one of the basic human needs. Meanwhile, in fact, from the data on the number of Sharia mortgage customers at Bank Jabar Syariah, namely the PPR IB Maslahah product for the 2017-2020 period, it fluctuated and tend to decrease. In addition, it needs a good financing risk management implemented by the company. The objective of this research is to find out how the risk management of financing and product management of PPR IB Maslahah Bank BJB Syariah KCP Kuningan. This study uses premier data from interviews conducted to several employees of Bank BJB Syariah KCP Kuningan, by triangulation technique. Meanshile, the results of this study are:1). The financing risk management carried out by Bank BJB Syariah is in accordance with the Financial Services Authority Regulation (POJK) Number 65 / POJK.03 / 2016 concerning the Implementation of Risk Management for Sharia Commercial Banks and Sharia Business Units as stated in article 3 in point c; 2) Management of PPR Products carried out by Bank BJB Syariah Kuningan has been implemented, however in fact they have limited authority from the headquarters. Â .